Extension of MF radar tidal measurements to E-region heights (95-125 km): Saskatoon (52°N, 107°W), Canada - S. P. Namboothiri (Annales Geophysicae, 1994)
Efforts have been made to extend the MF radar tidal profiles to E-region heights. The totally reflected MF radar echoes from E-region heights during daytime are known to be group-retarded and the corresponding wind and tidal data will have associated height discrepancies. The estimation of the E-region real heights (Namboothiri et al., 1993), and the elimination of the data for which the group retardation is significant, are selected as the basic criteria to extend the tidal profiles to 100-125 km. The analysis of the quiet (Ap<19) days of the winter and summer seasons of 1988/89 shows that the tidal propagation continues to higher altitudes with some changes in their pattern, e.g. longer wavelengths, compared to that in the lower altitudes. Comparison with the model profiles shows some resemblance and some disagreements. The reliability of the MF radar tidal measurements of E-region heights and the propagation of tides in this region have been discussed in the light of existing theories and other experimental observations. It is concluded that, based on the initial studies with UHF and MF systems and within the limits of the available theories, the information on tides presented here for the 100-125 km region using the MF radar observations is useful. Suggestions for future work in this direction are also given.